Esculetin inhibits the PI3K/Akt/mTOR pathway and enhances anti-colorectal cancer activity via binding to ENO1 - Ma, Jianing; Zhang, Miaomiao; Mulati, Shulipan; Nabi, Xinhua; Zhang, Weiyi (Frontiers in Pharmacology, 2025)
IntroductionColorectal cancer (CRC) ranks as the third most prevalent malignant tumor worldwide and is the second leading cause of cancer-related mortality. At present, while its standard treatment consists of a combination of surgery and chemotherapy, metastasis and recurrence are generally associated with a poor prognosis.MethodsFlow cytometry with Hoechst 33342 staining was employed to detect the changes in cell cycle and apoptosis in CRC cells. The molecular mechanisms of Esc’s antitumor properties were elucidated through network pharmacology, transcriptome sequencing technology, drug affinity responsive target stability (DARTS), and molecular docking. The in vivo antitumor effects of Esc were examined using the xenograft mouse model.ResultsIn this study, esculetin (Esc) exerted significant anti-proliferative effects across the CRC cell lines HCT116 and HT-29. Furthermore, Esc triggered cell death, arrested the HCT116 cell cycle at the S phase and the HT-29 cell cycle at the G0/G1 phase, inhibited the PI3K/Akt/mTOR signaling pathway, and promoted anti-CRC effects both in vitro and in vivo. Additional mechanistic investigations revealed that Esc bound to the ENO1 protein and altered its stability. Moreover, silencing ENO1 expression reversed the anti-CRC effect of Esc.DiscussionThis study highlighted the effects of Esc against CRC and clarified that Esc inhibits the PI3K/Akt/mTOR signaling pathway and enhances the anti-CRC activity by binding to ENO1, suggesting that ENO1 may become a potential target for the treatment of CRC. It may strengthen the evidentiary foundation for developing novel antitumor agents with enhanced efficacy and reduced toxicity.